VALUATION OF MOUNT MERAPI NATIONAL PARK: A TRAVEL COST ANALYSIS - Awan Setya Dewanta (Economic Journal of Emerging Markets, 2010)
This study estimates recreational value of Taman Nasional Gunung Merapi (TNGM – Mount MerapiNational Park) in Kaliurang, Yogyakarta with a travel cost method. Since the visitors are not the frequentones, the paper estimates the visitor’s utility using a categorical regression technique. Applyingin-depth interview on visitors from August 1st until August 15th 2009, the results suggest that the utilityfunction for recreation at volcano national park is better estimated using the negative binomialdistribution model. It also finds that the economic value of recreation at volcano national park is Rp222,000, and that the total consumer surplus for recreation national park is Rp 31.2 billion.Keywords: Travel cost valuation, binomial regression model, recreation national park valuationJEL classification numbers: D12, L83